The Relationship between Organizational Culture and Employee’s Job Satisfaction: A Case Study at A’Lamoda Silk House Sdn Bhd / Badura Bakri and Nor Farhana Muhamad - Bakri, Badura; Muhamad, Nor Farhana (2010)
The objective of this study is to identify the components of organizational culture that influence employees’ satisfaction. This study involves 66 staff of A’Lamoda Silk House Sdn. Bhd at Sungai Petani branch. There are three factors that will be discussed in this study as independent variables which are supervisions, reward and work environment. Those independent variables will be dependent on employee satisfaction as dependent variable. The consideration of components that influence employee satisfaction was engaged with customer satisfaction.